The National Minimum Wage and its interaction with the tax and benefits system: A focus on Universal Credit - Mike Brewer; Paola De Agostini (University of Essex, Institute for Social and Economic Research (ISER), 2015)
This paper uses the UK module of EUROMOD to examine the likely impact of Universal Credit (UC) on the incomes and work incentives of families containing NMW workers ("NMW families"). It in part updates previous work done for the Low Pay Commission (Brewer, May and Phillips, 2009). The analysis was completed after the 2012 Autumn Statement, but before the Spring 2013 Budget, and so does not reflect any changes to personal taxes and benefits for 2014-15 announced then.
Keywords: C15; H24; H31; H53; 330; microsimulation; income distribution; universal credit; national minimum wage; work incentives